Premorbid Functioning in Schizophrenia: A Controlled Study of Nigerian Patients (1994)
We compared the premorbid social adjustment of 38 schizophrenic patients with that of 20 manic patients. Even though the small sample size affected the number of significant differences obtained, schizophrenic patients consistently showed evidence of poorer premorbid functioning than manics at various stages of social development. Schizophrenic men also tended to have functioned more poorly than women. Poor premorbid functioning was associated with negative syndrome, but not with positive or disorganization syndromes. Our findings suggest that poor premorbid adjustment is an early sign of schizophrenic illness even among patient populations who may be characterized by good short-term outcome.